Kontribusi Platform Digital dalam Mengoptimalisasikan Pengumpulan dan Pendistribusian Zakat pada Kantor BAZNAS Kabupaten Pasaman - Rahmi Zikra; Andis Febrian (Lembaga Yasin AlSys, 2026)
The use of digital platforms in zakat management has received attention in various studies, but empirical studies that comprehensively integrate the aspects of zakat collection and distribution at the local level remain limited. This study aims to analyze the contribution of digital platforms in optimizing zakat collection and distribution at BAZNAS Pasaman Regency, as well as to identify the obstacles and opportunities in their implementation. This study used a qualitative approach with a case study design, involving informants drawn from BAZNAS administrators, muzakki, and mustahik selected through purposive sampling. Data were collected through in-depth interviews, observation, and documentation, and were then analyzed using thematic analysis techniques with the interactive model of Miles, Huberman, and Saldaña. The results showed that digital platforms, such as social media, bank transfers, and QRIS, contributed to increasing the ease, efficiency, and reach of zakat collection, although their utilization has not been evenly distributed across the community. In the distribution aspect, digital platforms played a role in the data collection and management of mustahik information in a more systematic manner, but their implementation was still limited to the administrative stage and had not been fully integrated. The main obstacles identified included low digital literacy, limited network infrastructure, and a level of public trust in digital systems that was not yet optimal, while the emerging opportunities included increased transparency, management efficiency, and expanded access to zakat services. These findings contribute to the development of digital-based zakat management theory and enrich the study of contemporary Islamic economics. The conclusion of this study emphasizes the importance of strengthening digital literacy, developing integrated systems, and increasing public trust in order to optimize technology-based zakat management.